Answer

Verified

340.2k+ views

**Hint:**In this problem we have given the equation of the circle and asked to find the centre, radius and the intercepts of the circle. From this we will convert the given equation in form of ${{\left( x-h \right)}^{2}}+{{\left( y-k \right)}^{2}}={{r}^{2}}$, where $\left( h,k \right)$ is the centre of the circle and $r$ is the radius of the circle. To convert the given equation, we will first rearrange the terms so that all the $x$ variables are at one place and all the $y$ variables are at one place. Now we will follow the method of completing squares and simplify the equation to convert it into required form. After converting the equation, we can write the centre and radius of the circle. Now we will calculate the intercepts by substituting $x=0$, $y=0$ in the circle equation and calculate the intercepts.

**Complete step by step solution:**

Given equation of the circle is ${{x}^{2}}+{{y}^{2}}+3x-6y+9=0$.

Rearranging the terms in the above equation, so that all the $x$ variable are at one place and all the $y$ variables are at one place. Hence the above equation is modified as

$\Rightarrow \left( {{x}^{2}}+3x \right)+\left( {{y}^{2}}-6y \right)+9=0$

Performing the completing squares method in the above equation, then we will get

$\Rightarrow \left( {{x}^{2}}+2\times \dfrac{3}{2}x \right)+\left( {{y}^{2}}-2\times 3y \right)+9=0$

Adding and subtracting the terms ${{\left( \dfrac{3}{2} \right)}^{2}}$, ${{3}^{2}}$ in the above equation, then we will get

$\begin{align}

& \Rightarrow \left( {{x}^{2}}+2\times \dfrac{3}{2}x \right)+\left( {{y}^{2}}-2\times 3y \right)+9+{{\left( \dfrac{3}{2} \right)}^{2}}-{{\left( \dfrac{3}{2} \right)}^{2}}+{{3}^{2}}-{{3}^{2}}=0 \\

& \Rightarrow \left( {{x}^{2}}+2\times \dfrac{3}{2}x+{{\left( \dfrac{3}{2} \right)}^{2}} \right)+\left( {{y}^{2}}-2\times 3y+{{3}^{2}} \right)+9-\dfrac{9}{4}-9=0 \\

\end{align}$

Applying the algebraic formulas ${{\left( a+b \right)}^{2}}={{a}^{2}}+2ab+{{b}^{2}}$, ${{\left( a-b \right)}^{2}}={{a}^{2}}-2ab+{{b}^{2}}$ in the above equation, then we will get

$\Rightarrow {{\left( x+\dfrac{3}{2} \right)}^{2}}+{{\left( y-3 \right)}^{2}}={{\left( \dfrac{3}{2} \right)}^{2}}$

Comparing the above equation with ${{\left( x-h \right)}^{2}}+{{\left( y-k \right)}^{2}}={{r}^{2}}$, then we will get

$\begin{align}

& -h=\dfrac{3}{2} \\

& \Rightarrow h=-\dfrac{3}{2} \\

\end{align}$ , $\begin{align}

& -k=-3 \\

& \Rightarrow k=3 \\

\end{align}$ , $\begin{align}

& {{r}^{2}}={{\left( \dfrac{3}{2} \right)}^{2}} \\

& \Rightarrow r=\dfrac{3}{2} \\

\end{align}$

Hence the centre of the circle is $\left( h,k \right)=\left( -\dfrac{3}{2},3 \right)$, radius is $r=\dfrac{3}{2}$.

Calculating the intercepts of the circle.

For $y$-intercept substituting $x=0$, in the equation of the circle, then we will get

$\begin{align}

& \Rightarrow {{\left( 0+\dfrac{3}{2} \right)}^{2}}+{{\left( y-3 \right)}^{2}}={{\left( \dfrac{3}{2} \right)}^{2}} \\

& \Rightarrow \dfrac{9}{4}+{{\left( y-3 \right)}^{2}}=\dfrac{9}{4} \\

& \Rightarrow {{\left( y-3 \right)}^{2}}=0 \\

& \Rightarrow y=3 \\

\end{align}$

We have only one $y$-intercept value that means the circle do not intercept the $y-axis$. It only touches the $y-axis$.

For $x$- intercept substituting $y=0$, in the equation of the circle, then we will get

$\begin{align}

& \Rightarrow {{\left( x+\dfrac{3}{2} \right)}^{2}}+{{\left( 0-3 \right)}^{2}}={{\left( \dfrac{3}{2} \right)}^{2}} \\

& \Rightarrow {{x}^{2}}+3x+\dfrac{9}{4}+9=\dfrac{9}{4} \\

& \Rightarrow {{x}^{2}}+3x+9=0 \\

\end{align}$

Discriminant of the above quadratic equation is

$\begin{align}

& \sqrt{{{b}^{2}}-4ac}=\sqrt{{{3}^{2}}-4\left( 1 \right)\left( 9 \right)} \\

& \Rightarrow \sqrt{{{b}^{2}}-4ac}=\sqrt{9-36} \\

& \Rightarrow \sqrt{{{b}^{2}}-4ac}=\sqrt{-27} \\

\end{align}$

From the above value we can say that the quadratic equation has no real solution, so there is no $x-$intercept for the circle. Now the graph of the circle will be

**Note:**We can also calculate the centre of the circle which is in form of $a{{x}^{2}}+b{{y}^{2}}+2gx+2fy+c=0$ is given by $\left( -\dfrac{g}{a},-\dfrac{f}{b} \right)$. So, we will compare the given equation with the $a{{x}^{2}}+b{{y}^{2}}+2gx+2fy+c=0$ and then write the centre of the circle.

Recently Updated Pages

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you arrange NH4 + BF3 H2O C2H2 in increasing class 11 chemistry CBSE

Is H mCT and q mCT the same thing If so which is more class 11 chemistry CBSE

What are the possible quantum number for the last outermost class 11 chemistry CBSE

Is C2 paramagnetic or diamagnetic class 11 chemistry CBSE

What happens when entropy reaches maximum class 11 chemistry JEE_Main

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Why is the adrenaline hormone called fight or flight class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Differentiate between lanthanoids and actinoids class 12 chemistry CBSE

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Give 10 examples of unisexual and bisexual flowers

Open circulatory system is present in I Arthropods class 12 biology CBSE

Name the highest peak of the Indian Himalayas class 8 social science CBSE